The “Algebra” Textbook by Kanysh Satpayev as a Source for the Formation of Kazakh Scientific Terminology - Zhubay Orynay; Uderbaev Almas; Absatar Adil (Progress in Science, 2026)
The beginning of the twentieth century marked an important stage in the formation of the Kazakh scientific language and the national terminological system. During this period, the Kazakh intelligentsia sought not only to develop the system of education but also to create a scientific language capable of conveying complex concepts from various fields of knowledge on the basis of the internal resources of the Kazakh language. Particular attention was paid to the development of terminology in the exact sciences, which was associated with the need to prepare textbooks and scientific literature in the native language. A significant contribution to the development of Kazakh scientific terminology was made by the outstanding scholar and academician Kanysh Satpayev. His activities encompassed not only the fields of geology and the organization of science in Kazakhstan, but also issues related to the development of the scientific language and the terminological system. One of the important pieces of evidence of this contribution is the textbook Algebra, in which the author sought to adapt mathematical concepts to the structure of the Kazakh language by employing its word-formation potential and creating national terminological equivalents.